2014
DOI: 10.1111/oik.01445
|View full text |Cite
|
Sign up to set email alerts
|

Land‐use legacies and present fire regimes interact to mediate herbivory by altering the neighboring plant community

Abstract: Past and present human activities, such as historic agriculture and fire suppression, are widespread and can create depauperate plant communities. Although many studies show that herbivory on focal plants depends on the density of herbivores or the composition of the surrounding plant community, it is unclear whether anthropogenic changes to plant communities alter herbivory. We tested the hypothesis that human activities that alter the plant community lead to subsequent changes in herbivory. At 20 sites distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 53 publications
2
38
0
Order By: Relevance
“…Nonagricultural and post-agricultural habitats each support a different assemblage of plants (Flinn andVellend 2005, Brudvig et al 2013) and grasshoppers (Hahn and Orrock 2015b). In a previous experiment conducted in non-experimental patches with intact canopies we found that herbivory rates were greater in post-agricultural sites and this was driven largely by the amount of alternative resources (plant material) available for herbivores to consume, with the highest rates of herbivory at intermediate levels of plant cover (Hahn and Orrock 2015a). Within our experimental landscapes, we use herbivore exclosures to quantify herbivory by grasshoppers on the growth of four species of perennial herbs to evaluate possible changes in herbivory at different distances from the resulting habitat edges .…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Nonagricultural and post-agricultural habitats each support a different assemblage of plants (Flinn andVellend 2005, Brudvig et al 2013) and grasshoppers (Hahn and Orrock 2015b). In a previous experiment conducted in non-experimental patches with intact canopies we found that herbivory rates were greater in post-agricultural sites and this was driven largely by the amount of alternative resources (plant material) available for herbivores to consume, with the highest rates of herbivory at intermediate levels of plant cover (Hahn and Orrock 2015a). Within our experimental landscapes, we use herbivore exclosures to quantify herbivory by grasshoppers on the growth of four species of perennial herbs to evaluate possible changes in herbivory at different distances from the resulting habitat edges .…”
Section: Introductionmentioning
confidence: 76%
“…The opposite pattern can also occur, where herbivory rates are greater in shade habitats (Muth et al 2008, Hakes andCronin 2012), presumably because plant defenses are lower than in shady habitats while herbivores are still present (Muth et al 2008). Alternatively, shady habitats can reduce overall herbaceous cover making the rare herbaceous plants that do persist in a shaded habitat more vulnerable to herbivory Cronin 2012, Hahn andOrrock 2015a). The varied results of these studies may be because studies generally only examine a single edge type (but see Wolf and Batzli 2004), include only one or a few focal species, and rarely experimentally manipulate both the edges and the quality of the adjacent patch.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grasshoppers are common invertebrate herbivores in our system (Evans et al . ; Hahn & Orrock ) and include the most likely insect consumers of the focal plant species. The two most common species of grasshoppers at our site are Melanoplus angustipennis (subfamily: Melanoplinae) and Schistocerca alutacea (subfamily: Cyrtacanthacridinae; Hahn & Orrock ), both species are mixed feeders that can eat a variety of grasses and forbs (Joern ).…”
Section: Methodsmentioning
confidence: 99%
“…We also hypothesized that, (ii) because plants in thinned patches grow faster compared to plants in unthinned patches (Harrington ), herbivory should have less of an effect on plant performance in thinned patches. Based on previous findings (Hahn & Orrock ), we predicted that (iii) herbivory would have greater effects where alternative plant resources are low, particularly in post‐agricultural sites. Collectively, we expected herbivory to have the greatest effect on juvenile plant survival in unthinned, post‐agricultural habitats.…”
Section: Introductionmentioning
confidence: 95%